ANALISIS HISTORIS DAN KONTEKSTUAL TERHADAP KISAH AL-QUR’AN: ANTARA FAKTA DAN MITOS - Miftakhussurur, Miftakhussurur; Aji Swasono, Pangestu (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2024)
This study examines the historicity of stories in the Qur'an to address debates about whether these narratives are historical facts or myths. The research aims to analyze the use of dalil naqli, including the Qur'an, Hadith, and consensus of scholars (ijma'), to support the factual paradigm while critiquing the myth paradigm that questions the authenticity of Qur'anic stories. The method employed is contextual critical historical analysis, using a qualitative approach based on library research. The findings reveal that the stories in the Qur'an are historical facts, validated through Qur'anic texts affirming their truth, corroborated by Hadith, and supported by the consensus of scholars. These narratives not only feature compelling accounts but also hold significant ibrah (lessons), offering spiritual, moral, and social guidance for readers. Conversely, the myth paradigm, which views Qur'anic stories as mere fabrications, risks eroding their educational value and undermining the Qur'an's authority as a holy scripture. This research makes a critical contribution by affirming the Qur'an's status as a source of knowledge containing historical truths, while also highlighting the enduring relevance of its lessons for human life. The findings strengthen the understanding that Qur'anic stories serve not only as spiritual learning tools but also as authentic evidence of historical narratives, thereby playing a vital role in enhancing the faith and comprehension of the Qur'an's magnificence among believers.